2004
DOI: 10.1016/j.jcrs.2003.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Laser in situ keratomileusis for hyperopia with the LADARVision 4000 with centration on the coaxially sighted corneal light reflex

Abstract: Hyperopic LASIK with LADARVision 4000 with the ablation zone centered on the coaxially sighted corneal light reflex did not adversely affect BSCVA and BSCCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
0
13
1
2
Order By: Relevance
“…These levels coincide with reports by Zadok et al [2] (≥20/20, 29.3%; ≥20/40, 85.7%), Desai et al [5] (≥20/20, 34.1%; ≥20/40, 87.8%), and Göker et al [19] (≥20/20, 14.81%; ≥20/40, 66.66%). However, levels reported by Cobo-Soriano et al [7] (≥20/20, 46.8%; ≥20/40, 93%), Waring et al [15] (≥20/20, 70.1%; ≥20/40, 99.3%), and Nepomuceno et al [20] (≥20/20, 44.4%; ≥20/40, 88.9%) were better than those achieved in our study. The low proportion of eyes having a UCVA of 20/20 or better at the end of followup was attributed to the relatively significant number of eyes having preoperative astigmatism of ≥0.50 D (0.5 D: 14.71%, 0.75 D: 2.94%, 1.0 D: 17.65%, 1.5 D: 14.71%, 2.25 D 2.94%, 3.0 D 8.82%).…”
Section: Discussioncontrasting
confidence: 86%
“…These levels coincide with reports by Zadok et al [2] (≥20/20, 29.3%; ≥20/40, 85.7%), Desai et al [5] (≥20/20, 34.1%; ≥20/40, 87.8%), and Göker et al [19] (≥20/20, 14.81%; ≥20/40, 66.66%). However, levels reported by Cobo-Soriano et al [7] (≥20/20, 46.8%; ≥20/40, 93%), Waring et al [15] (≥20/20, 70.1%; ≥20/40, 99.3%), and Nepomuceno et al [20] (≥20/20, 44.4%; ≥20/40, 88.9%) were better than those achieved in our study. The low proportion of eyes having a UCVA of 20/20 or better at the end of followup was attributed to the relatively significant number of eyes having preoperative astigmatism of ≥0.50 D (0.5 D: 14.71%, 0.75 D: 2.94%, 1.0 D: 17.65%, 1.5 D: 14.71%, 2.25 D 2.94%, 3.0 D 8.82%).…”
Section: Discussioncontrasting
confidence: 86%
“…The authors stressed the importance of centering over the CSCLR for hyperopes due to a large angle kappa, and also because hyperopes have smaller functional optical zones and less tolerance of decentration. [25] Several years later, Kanellopoulos also reported a good safety profile when centering on the CSCLR to accommodate for angle kappa. In addition, he reported a significant postoperative improvement in uncorrected visual acuity and an increase in best spectacle corrected visual acuity (BSCVA).…”
Section: Methodsmentioning
confidence: 99%
“…[39] However, other authors have suggested that angle kappa in myopia is usually negligible. [1925] A full discussion of the centration techniques in myopia is beyond the scope of this article but two studies deserve mention. Arbelaez et al compared LASIK centered over the pupil to LASIK centered over the corneal vertex in 52 myopic patients with a moderate to large angle kappa.…”
Section: Methodsmentioning
confidence: 99%
“…2,3,6,11 Changes up to 0.269 mm (mean 0.086 mm) in the pupil center under photopic and mesopic light conditions in 92 myopic eyes measured with an infrared pupillometer have been reported. 9 These challenges can be overcome by centering on the coaxially sighted corneal light reflex, which is independent of pupil size.…”
Section: Discussionmentioning
confidence: 94%
“…For example, centering the laser ablation on the pupil center (line of sight) in a patient with a large angle k. 2,3 Decentered ablations resulting from angle k have been reported after myopic laser ablation. 4 Historically, based on experience with radial keratotomy and the belief that mild angle k in myopia does not warrant recentering, the line of sight, not the visual axis (or coaxially sighted corneal light reflex), has been the preferred centering landmark for myopic laser ablation.…”
mentioning
confidence: 99%